Carotenoid, chlorophyll, and chlorophyll-derived compounds in grapes and Port Wines - Pinto, Maria Manuela Mendes (2011)
Carotenoids and chlorophyll-derived compounds in grapes and Port wines were investigated by HPLCDAD and HPLC-DAD-MS (ESP+) analysis. A total of 13 carotenoid and chlorophyll-derived compounds are formally reported in grapes, 3 are identified for the first time, pheophytins a and b and (13β-carotene, and 3 others remain unknown. In Port wines 19 compounds with carotenoid or chlorophylllike structures are present, 8 still unidentified. The young wines showed higher total carotenoid content and chlorophyll-like compounds compared to aged Ports, with lutein and β-carotene as major carotenoids. Among samples analyzed of monovarietal Vitis vinifera L. cultivar wines produced with the five most important Douro varieties, Tinta Roriz contained the highest levels of carotenoids and Touriga Franca the lowest. The forced-aging study indicated that lutein was more sensitive to temperature than β-carotene. Additionally, aged wines showed higher ratios of β-carotene/lutein concentrations compared to new Ports. Rates of degradation of chlorophyll derivative compounds were higher than those for carotene and lutein.